Wide input-voltage range boost three-level DC-DC converter with quasi-Z source for fuel cell vehicles - Zhang, Yun; Shi, Jilong; Zhou, Lei; Li, Jing; Sumner, Mark; Wang, Ping; Xia, Changliang (IEEE, 2017)
To solve the problem of the mismatched voltage levels between the dynamic lower voltage of the fuel cell stack and the required constant higher voltage (400V) of the DC link bus of the inverter for fuel cell vehicles, a Boost three-level DC-DC converter with a diode rectification quasi-Z source (BTL-DRqZ) is presented in this paper, based on the conventional flying-capacitor Boost three-level DC-DC converter. The operating principle of a wide range voltage-gain for this topology is discussed according to the effective switching states of the converter and the multi-loop energy communication characteristic of the DRqZ source. The relationship between the quasi-Z source net capacitor voltages, the modulation index and the output voltage, is deduced and then the static and dynamic self-balance principle of the flying-capacitor voltage is presented. Furthermore, a Boost three-level DC-DC converter with a synchronous rectification quasi-Z source (BTL-SRqZ) is additionally proposed to improve the conversion efficiency. Finally, a scale-down 1.2 kW BTL-SRqZ prototype has been created, and the maximum efficiency is improved up to 95.66% by using synchronous rectification. The experimental results validate the feasibility of the proposed topology and the correctness of its operating principles. It is suitable for the fuel cell vehicles.